Bioconcrete: A review of its application in civil construction (Research, Society and Development, 2021)
Concrete is one of the most consumed materials in the world, second only to water, due to its importance in civil construction. In general, concrete basically consists of a mixture of cement, water and aggregates (coarse and fine). Currently, other special concretes are already being used, formed by, besides the mentioned mixture, materials classified as additives, which aims to enhance properties and characteristics of the concrete. In this sense, the concern with the quality of this material makes it the object of advanced studies, aiming at seeking its best performance and structural durability. In view of this, this article presents a bibliographic review on the use of bioconcrete in civil construction. It aims to introduce the concept of bioconcrete as a sustainable technological alternative, which allows providing self-repair of pathological problems, such as minimizing cracks present in concrete structures. The research was developed from a bibliographic review on the subject, passing through a general approach, presenting the origin, statistical data, applicability and technological characteristics about the theme. It is concluded with emphasis the importance of studying efficient methods to promote and improve the self-curing capacity of concrete, besides increasing the use of more sustainable materials in civil construction sector.